If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 2 + b + 3 Reorder the terms: 8 = 2 + 3 + b Combine like terms: 2 + 3 = 5 8 = 5 + b Solving 8 = 5 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. 8 + -1b = 5 + b + -1b Combine like terms: b + -1b = 0 8 + -1b = 5 + 0 8 + -1b = 5 Add '-8' to each side of the equation. 8 + -8 + -1b = 5 + -8 Combine like terms: 8 + -8 = 0 0 + -1b = 5 + -8 -1b = 5 + -8 Combine like terms: 5 + -8 = -3 -1b = -3 Divide each side by '-1'. b = 3 Simplifying b = 3
| 5-3m=11 | | 12x+131=189+3x | | -16=p-6 | | X+37=46 | | 2(n+3)=2 | | 5m+6m+2+4m+8+3m=82 | | -4-2m=12 | | -k+-7=3k+1 | | (4x-3)(2x+4)=0 | | n+4=-30 | | 7x-18=21+4x | | 4-2x=-5x-11 | | 2p+4q=24 | | 0+50*1-60-60*0*10= | | 182.99=2.87w+14.04 | | c=2.87(60)+14.04 | | c=2.87(30)+14.04 | | Xx-5=11 | | c=2.87(13)+14.04 | | c=2.87(10)+14.04 | | 7x^2-29x=0 | | c=2.87(3)+14.04 | | 2(2.5+3)= | | 10+h=4h-14 | | K=3w+12 | | -6x*9x= | | 2x^2-4x-3=x | | -2(-4+x)=-8 | | (-2y)*(3x)= | | 6x+10=37-3x | | -1+2k=5 | | 5x*(-16x)= |